Islamic home financing questions in Sabah, Sarawak - Amin, Hanudin (Borneo Post (KK), 2016)
ACCORDING to Bank Negara Malaysia (2016), the consumers' total debt values for Islamic home financing, Islamic personal financing and Islamic credit card were RM107,060.0 million, RM32,499.6 million and RM2.487.6 million respectively. All figures were reported for the year 2016. This trends demonstrate that Islamic home financing is much more vital than its peers. It is in line with the belief that it is needed for home ownership that is considered as a basic need in our modern life. To Sabahans and Sarawakians, buying a house is a key milestone that tops their lifetime to do lists and perhaps their list of financialfears. With a window shopping, however, one has a leeway to manage the house buying process effectively.